Meningkatkan Partisipasi Peserta Didik dalam Pembelajaran Melalui Metode Index Card Match - Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2025)
Low student participation in classroom learning often results in limited engagement, both physically and mentally, which negatively affects the overall effectiveness of the teaching and learning process. This issue was identified among the third-grade students of SDN Model Terpadu Madani, where learners showed minimal involvement in asking questions, expressing opinions, and collaborating during lessons. This study aims to improve student learning participation through the implementation of the Index Card Match (ICM) method as an active learning strategy. The research employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. Data were collected through observation and analyzed using descriptive quantitative techniques. The results demonstrated a significant improvement in student participation, with an initial rate of 43.24% in Cycle I (categorized as sufficient) increasing to 65.42% in Cycle II (categorized as good). All participation indicators—questioning, expressing opinions, responding to questions, and group collaboration—showed notable progress. Based on these findings, the Index Card Match method is proven effective in enhancing student participation and is recommended as a viable active learning strategy for elementary school classrooms.